Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1007/s13312-023-2887-0
|View full text |Cite
|
Sign up to set email alerts
|

Multisystem Inflammatory Syndrome in Children (MIS-C) Associated With COVID-19–Single-Center Experience

Abstract: Objectives To describe the clinical presentation, phenotype and outcome of multisystem inflammatory syndrome in children (MIS-C) associated with coronavirus disease 2019 (COVID-19) from a tertiary care center in southern India. Methods 257 children fulfilling the inclusion criteria of MIS-C were prospectively enrolled from June, 2020 to March, 2022. Results Median (range) age at presentation was 6 year (35 day to 12 years). Presenting feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…Severe myocardial dysfunction has been reported as a common cardiac abnormality in children with MIS-C [18]. Studies have also reported that coronary abnormalities were seen in 45.9% of MIS-C children, and the majority of cases display left ventricular dysfunction normalized before discharge [19]. A recent study from Poland reported that the majority of children had echocardiographic features of cardiovascular involvement in the course of MIS-C, but the majority of children with acute heart failure improved significantly within a few days of treatment [20].…”
Section: Discussionmentioning
confidence: 99%
“…Severe myocardial dysfunction has been reported as a common cardiac abnormality in children with MIS-C [18]. Studies have also reported that coronary abnormalities were seen in 45.9% of MIS-C children, and the majority of cases display left ventricular dysfunction normalized before discharge [19]. A recent study from Poland reported that the majority of children had echocardiographic features of cardiovascular involvement in the course of MIS-C, but the majority of children with acute heart failure improved significantly within a few days of treatment [20].…”
Section: Discussionmentioning
confidence: 99%